Hypersensitivity reaction associated with subcutaneous glargine insulin therapy in a cat. Issue 2 (November 2016) - Murphy, Lisa A; Zuendt, Greg F; Nakamura, Reid K; Gambardella, Paul
Case summary: A 14-year-old, domestic shorthair cat was treated for transient diabetes mellitus for 3 months with glargine insulin, which was discontinued when the diabetes mellitus resolved. Approximately 36 months later the diabetes mellitus recurred and glargine insulin was restarted. Within 2–3 mins of the first injection the cat collapsed, developed profuse vomiting and diarrhea, as well as facial swelling and diffuse erythema. A hypersensitivity reaction was suspected and the cat was treated with antihistamines, aggressive fluid therapy and gastrointestinal support. The cat made a full recovery and was discharged 3 days later. Six months later the cat re-presented for relapse of its diabetes mellitus and an intradermal skin challenge with 1:20 diluted insulin was performed confirming a hypersensitivity to glargine. The cat continues to be well regulated on porcine zinc insulin without any hypersensitivity reactions noted. Relevance and novel information: Hypersensitivity reactions to insulin administration are rarely described in human medicine. This is the first reported case of a hypersensitivity reaction secondary to glargine insulin in a cat. Clinicians should be aware of this potential complication, particularly in animals with a previous history of insulin administration and the potential to utilize intradermal testing with insulin.